Irrational use of emergency and your risks to women’s health (Research, Society and Development, 2022)
Introduction: Emergency contraceptives, known as "morning after pills", belong to the class of drugs used to prevent unwanted pregnancy. Excessive use of EC can cause several health problems and should be used in extreme need. Objective: To observe the abusive use of emergency contraceptives and the months with the highest rates of use. Methodology: This is a descriptive, qualitative research with a review of available scientific studies, in order to observe the consequences of excessive use and greater demands in 10 pharmacies in downtown Rio de Janeiro in order to record the months with the highest purchase rate. Final Considerations: The consequences of abusive use, the contraindications and diseases linked to this abuse were observed. The topic is extremely important and should be further addressed in scientific research. Based on the material collected, it was possible to conclude that the seasonality of purchases occurred sporadically between February and November.